Optimalisasi Daya Ingat Anak Melalui Permainan Puzzle: Studi Eksperimen - Stacya A, Oey Michelle; Amaliyah, Shofwatun (Universitas Pahlawan Tuanku Tambusai, 2025)
The observation that children's memorization abilities are still quite low when playing games is the driving force for this research. This study takes the form of descriptive action research in the classroom. One educator and ten students participated in the study. Research and data analysis have shown that: 1) The teacher's lesson plan for enhancing the memory skills of 5- and 6-year-olds at Fatima Kindergarten Semarang through the use of puzzle games is of a